Cyberbullying Behaviour: A Study of Undergraduate University Students - Shaikh, F.B. (Institute of Electrical and Electronics Engineers Inc., 2021)
Higher education requires access to Information and communication technologies (ICT's). This exposure and access to ICT, coupled with the excessive usage of social media, has augmented the problem of cyberbullying among university students. Previous studies have investigated cyberbullying among school students while overlooking university students, who are actually more engaged in cyberbullying perpetration. In view of the gravity of the situation and its impact on the wellbeing of the university students, this study aims to understand the role of personal and psychological factors dragging Malaysian undergraduate students of public and private universities towards cyberbullying behaviour. In order to develop the framework, the study has utilized the 'Theory of planned behavior' and 'Social Cognitive Theory'. The study is based on a quantitative research approach and employs a self-administered survey to collect data. The data has been analyzed through the Structured Equation Modeling (SEM) technique using SmartPLS. The results reveal that individual factors including cyberbullying awareness and personality traits are not associated with Malaysian undergraduate students' cyberbullying behaviour. However, psychological factors, including self-esteem, internalizing behavior, and anti-social behavior, play an instrumental role in developing Malaysian undergraduate students' cyberbullying attitude. The study also confirms that subjective norms assert a powerful positive impact on cyberbullying attitude of Malaysian undergraduates. Lastly, the study aims to contribute to the research on cyberbullying behavior by offering a conceptual validated model that predicts Malaysian university students' cyberbullying behavior. This study also found that social media usage plays moderating role between cyberbullying intention and cyberbullying behavior. Parents, universities, and governments will benefit from this study by understanding factors to be considered when making a policy to reduce cyberbullying among university students. Â© 2013 IEEE.